(untitled) (TAJ: Journal of Teachers Association, 2009)
Hepatitis B virus infection is an important public health problem with significant morbidity and mortality. Recombinant hepatitis B vaccine for the prevention of hepatitis B virus infection is in practice in different parts of the world since its availability in 1986. Government of Bangladesh has also included hepatitis B vaccine in EPI schedule since 2005. This study was carried out to assess the seroconversion status among hepatitis B vaccinated individuals. A total of 190 individuals including 150 vaccinated persons and 40 non-vaccinated apparently healthy individuals were included as study population. Sources of vaccinated persons were from both EPI and non-EPI schedule of vaccination. Age and sex matched non-vaccinated individuals served as controls for the study. All individuals constituting the study population were screened for HBsAg by Immunochromatographic strip test and only HBsAg-negative persons were included for estimation of their anti-HBs titer. Out of 150 vaccinated individuals, 133(88.67%) were found to have anti-HBs titer in the protective level (≥10 IU/L), while 17(11.33%) individuals had anti-HBs titer below the protective level (<10 IU/L). All non-vaccinated controls had anti-HBs titers below the protective level. Regarding immune response developed among vaccinated individuals, 67.78%, 23.33% and 8.89% were good-responders, hypo-responders and nonresponders respectively. Mean titer of anti-HBs was found significantly higher among recipients who received booster dose than those who received 3 doses schedule (863.39 IU/L vs. 262.40 IU/L), indicating high antibody titer develops after booster dose. Vaccinated group included 85 (56.67%) men and 65 (43.33%) women with protective level of anti-HBs titer found in 85.88% male and 92.31% female individuals. Vaccinated individuals from lower socioeconomic condition have had comparatively low rate of protective antibody than people from middle and upper classes. Recombinant HB vaccine induces good level of protective immunity among vaccinated persons. The present study showed that the proportion of adults (93.33%) developed level of protective antibody titer was higher than that of children (83.33%). It indicates that there is difference of antibody titer between children and adults after recombinant Hepatitis B vaccination. doi: 10.3329/taj.v21i1.3210 TAJ 2008; 21(1): 1-11